APPLICATION OF THE TOPSIS DECISION MODEL FOR EVALUATING SUSTAINABILITY OF RAINWATER HARVESTING SYSTEM IN AWKA URBAN, NIGERIA - Okadigwe Emmanuel Igwebudu; Chukwuma Emmanuel Chibundo; Ogbuagu Nneka Juliana; Nwanna Emmanuel Chukwudi (Universitas Ngeri Malang, 2026)
The abstract should be written in both English and Indonesian in one paragraph consists of maximum 250 words. The abstract should explain the purpose, method, and the result of the research concisely. An abstract should stand alone, means that no citation in the abstract. The abstract should be written in both English and Indonesian in one paragraph consists of maximum 250 words. The abstract should explain the purpose, method, and the result of the research concisely. An abstract should stand alone, means that no citation in the abstract. The abstract should be written in both English and Indonesian in one paragraph consists of maximum 250 words. The abstract should explain the purpose, method, and the result of the research concisely. An abstract should stand alone, means that no citation in the abstract. The abstract should be written in both English and Indonesian in one paragraph consists of maximum 250 words. The abstract should explain the purpose, method, and the result of the research concisely. An abstract should stand alone, means that no citation in the abstract.